Panic disorder with agoraphobia from a behavioral neuroscience perspective: Applying the research principles formulated by the Research Domain Criteria (RDoC) initiative. (March 2016) - Hamm, Alfons O.; Richter, Jan; Pané‐Farré, Christiane; Westphal, Dorte; Wittchen, Hans‐Ulrich; Vossbeck‐Elsebusch, Anna N.; Gerlach, Alexander L.; Gloster, Andrew T.; Ströhle, Andreas; Lang, Thomas; Kircher, Tilo; Gerdes, Antje B. M.; et al.
Abstract: In the current review, we reconceptualize a categorical diagnosis—panic disorder and agoraphobia—in terms of two constructs within the domain "negative valence systems" suggested by the Research Domain Criteria initiative. Panic attacks are considered as abrupt and intense fear responses to acute threat arising from inside the body, while anxious apprehension refers to anxiety responses to potential harm and more distant or uncertain threat. Taking a dimensional view, panic disorder with agoraphobia is defined with the threat‐imminence model stating that defensive responses are dynamically organized along the dimension of the proximity of the threat. We tested this model within a large group of patients with panic disorder and agoraphobia ( N  = 369 and N  = 124 in a replication sample) and found evidence that panic attacks are indeed instances of circa strike defense. This component of the defensive reactivity was related to genetic modulators within the serotonergic system. In contrast, anxious apprehension—characterized by attentive freezing during postencounter defense—was related to general distress and depressive mood, as well as to genetic modulations within the hypothalamic‐pituitary‐adrenal (HPA) axis. Patients with a strong behavioral tendency for active and passive avoidance responded better to exposure treatment if the therapist guides the patient through the exposure exercises.